Lectotype designations, taxonomic notes and new synonymies in some species of the bee genus Centris Fabricius, 1804 described by Amédée Lepeletier de Saint-Fargeau (Hymenoptera: Apidae) - Vivallo, Felipe (Zootaxa, 2019)
In this paper the primary types of Centris described by Amédée Lepeletier de Saint-Fargeau in 1841 deposited at Muséum National d’Histoire Naturelle, France and Hope Entomological Collection, Oxford University Museum of Natural History, United Kingdom were studied. To stabilize the application of some names, lectotypes were designated for C. bimaculata, C. collaris, C. decolorata, C. denudans, C. dorsata, C. ferruginea, C. fuscata, C. maculata (= C. decolorata), C. obsoleta, C. picea, C. poecila, C. trigonoides, C. violacea and C. vittata. Centris picea nomen oblitum is withdrawn from the synonymy of C. lanipes (Fabricius) and proposed as new junior synonym of C. trigonoides nomen protectum. Centris nigrescens is removed from the synonymy of C. vittata and revalidated, proposing C. merrillae Cockerell and C. lanipes ogilviei Cockerell as its new junior synonymies. Lectotypes for this latter species and for C. rubella Smith (= C. ferruginea) were also designated. In addition, due to the impossibility of identifying C. thoracica and the misplacement of its type material, it is proposed to consider it nomen dubium and place it incertae sedis.